HIV community viral load trends in South Carolina. (March 2017) - Chakraborty, Hrishikesh; Weissman, Sharon; Duffus, Wayne A; Hossain, Akhtar; Varma Samantapudi, Ashok; Iyer, Medha; Albrecht, Helmut
Community viral load is an aggregate measure of HIV viral load in a particular geographic location, community, or subgroup. Community viral load provides a measure of disease burden in a community and community transmission risk. This study aims to examine community viral load trend in South Carolina and identify differences in community viral load trends between selected population subgroups using a state-wide surveillance dataset that maintains electronic records of all HIV viral load measurements reported to the state health department. Community viral load trends were examined using random mixed effects models, adjusting for age, race, gender, residence, CD4 counts, HIV risk group, and initial antiretroviral regimen during the study period, and time. The community viral load gradually decreased from 2004 to 2013 ( p  < 0.0001). The number of new infections also decreased ( p  = 0.0001) over time. A faster rate of decrease was seen among men compared to women ( p  < 0.0001), men who have sex with men ( p  = 0.0001) compared to heterosexuals, patients diagnosed in urban areas compared to that in rural areas ( p  = 0.0004), and patients prescribed single-tablet regimen compared to multiple-tablet regimen ( p  < 0.0001). While the state-wide community viral load decreased over time, the decline was not uniform among residence at diagnosis, HIV risk group, and single-tablet regimen versus multiple-tablet regimen subgroups. Slower declines in community viral load among females, those in rural areas, and heterosexuals suggest possible disparities in care that require further exploration. The association between using single-tablet regimen and faster community viral load decline is noteworthy.